PEMAHAMAN MAHASISWA DAN KARYAWAN TERHADAP ADIPURA - Hadinoto, Hadinoto; Suhesti, Eni (Wahana Forestra: Jurnal Kehutanan, 2016)
One of the government's efforts in maintaining the ecological balance in urban areas is to give an award in the form of "ADIPURA" to the cities judged to meet criteria such as; hygiene, beauty, beauty, comfort, green and other environmental aspects. The purpose of research is to identify the level of understanding of students and employees of the University Lancang Kuning Pekanbaru. Primary data was col lected through interviews with respondents using the help of questionnaires (attached). Determination of the respondents were randomized (random sampling) for each faculty (S1). The number of respondents who were taken as many as 30 students and 30 employe es. Data obtained from filling the questionnaire will be processed in the following manner; the number of questions in questionnaires of 20 questions. Each question provided three answers for respondents to choose according to their understanding. To quant ify the data by using a Likert scale, which is any of respondents who are knowledgeable about Verse (answer "Yes") rated 3, which is not yet fully understood (answered "Doubt") was given a value of 2 and that does not understand (answered "No") by a value of 1. the data obtained will be analyzed descriptively, the depiction of data obtained as it is, without any lawyer-generalisasian. Data will be illustrated through tables or graphs. Based on the research results can be summarized as follows: (1) the level of student understanding of the Lancang Kuning University adipura for high category (33.33%), moderate (56.67%) and low (10%); (2) the level of employees' understanding of the Lancang Kuning University adipura for high category (63.33%) and moderate (36.67%).